Anti-C1q antibody in patients with lupus nephritic flare: 18-month follow-up and a nested case-control study. Issue 2 (3rd March 2016) - Fatemi, Alimohammad; Samadi, Golnaz; Sayedbonakdar, Zahra; Smiley, Abbas
Abstract: Objectives : A prospective cohort was conducted to investigate the association of anti-C1q antibody and lupus/lupus nephritis (LN) flare. Methods : Sixty-nine consecutive patients with systemic lupus erythematosus were enrolled and followed up for 18 months. Anti-C1q was recorded at the first visit and at the time of flare. For patients with flare, age and sex matched SLE patients were considered as the control group (nested case-control study). The predictability of anti-C1q and other laboratory indices for LN flare during the 18-month follow-up was calculated. Results : Fourteen out of sixty-nine (20%) had lupus flare. Fourteen patients were chosen as controls. Nine cases and three controls had positive anti-C1q at the first visit ( p =  0.0001). Twenty-six (38%) and 43 (62%) patients had positive and negative anti-C1q antibody at the first visit, respectively, of whom 9 (34.5%) and 3 (7%) patients developed LN flare in the next 18 months ( p =  0.003). Anti-C1q and 24-hour urine protein were found as the main predictors of LN flare. The positive and negative predictive values of anti-C1q for LN flare were 35% and 93%, respectively. Predictive values of positive anti-C1q/low C3 together were 60% and 96%, respectively. Conclusion : The combination of positive anti-C1q/low C3 had the highest reasonable predictive values for LN flare.